A Distance-Reduction Trajectory Tracking Control Algorithm for a Rear-Steered AGV - Anugrah K Pamosoaji (Computer Engineering and Applications Journal, 2018)
This paper presents a Lyapunov-based switched trajectory tracking control design for a rear-steered automated guided AGV (AGV). Given a moving reference whose position and orientation have to be tracked by the AGV, the main objective of the controller is to reduce AGV’s distance from the reference while adjusting its orientation. The distance reduction issue is important, especially in huge warehouses operating a group of AGVs, since the rate of AGV-to-reference distance reduction contributes to the possibility of AGV-to-AGV collision. A set of control algorithms is proposed to handle large AGV’s orientation. Simulations that show the performance of the proposed method is presented.